(Un)Hidden Figures: A Synthesis of Research Examining the Intersectional Experiences of Black Women and Girls in STEM Education. Issue 1 (March 2018) - Ireland, Danyelle T.; Freeman, Kimberley Edelin; Winston-Proctor, Cynthia E.; DeLaine, Kendra D.; McDonald Lowe, Stacey; Woodson, Kamilah M.
In this chapter, we argue that intersectionality is a theoretical and methodological framework by which education researchers can critically examine why and how students in STEM fields who are members of intersecting marginalized groups have distinctive experiences related to their social identities, other psychological processes, and educational outcomes. Taken separately, the bodies of education research focused on the experiences of Black students and female students in STEM fields often render Black women and girls "hidden figures" in that they have not sufficiently addressed their simultaneous racialized and gendered experiences in educational contexts. Additionally, we find that the current discourse on intersectionality is limited in that it does not attend to key psychological processes associated with identity and the intersectional experience in STEM education. We take a theoretical and methodological approach to examining intersectionality in STEM education and provide a new interpretation of the literature on Black women and girls in this social context. A synthesis of ( N = 60) research studies revealed that (1) identity; (2) STEM interest, confidence, and persistence; (3) achievement, ability perceptions, and attributions; and (4) socializers and support systems are key themes within the experiences of Black women and girls in STEM education. Our analysis also highlights the ways that researchers have employed intersectionality to make the experiences of Black women and girls in STEM education more visible, or "unhidden." We discuss these findings from a psychological perspective and provide insights to guide future research and practice directions in STEM education.